تأثير تطبيق سياسة الرعاية التمريضية على النتائج السريرية للوصلة الشريانية الوريدية بعد العمل الجراحي لدى مرضى الداء الكلوي النهائي - حيدر مازن; عباس عبد الفتاح; احمد نورا (Latakia University Journal -Medical Sciences Series, 2016)
بالرغم من أن مضاعفات الوصلة الشريانية الوريدية قليلة الحدوث إلا أنها تحدث، وتعتبر أهم المضاعفات والأكثر شيوعا هي التخثر والإنتان النزف والتضيق الوعائي وتشكل أم دم ونقص التروية،وقد لوحظ أن التحضير والعناية الجيدة بالوصلة الشريانية الوريدية لها دور مهم في التقليل من حدوث المضاعفات إضافة إلى تسريع نضوج الوصلة الشريانية الوريدية.يساهم تطبيق سياسة الرعاية التمريضية بالوصلة الشريانية الوريدية بعد العمل الجراحي بشكل كبير في منع حدوث المضاعفات وتسريع النضوج.الهدف: أجريت هذه الدراسة لتحديد تأثير تطبيق سياسة الرعاية التمريضية على النتائج السريرية للوصلة الشريانية الوريدية بعد العمل الجراحي لدى مرضى الداء الكلوي النهائي. أدوات البحث و طرائقه: أجري البحث على عينة قوامها 20 مريضاً في قسم التحال الكلوي وقسم الجراحة في مشفى الأسد الجامعي (اللاذقية). تم تقييم النتائج السريرية للوصلة الشريانية الوريدية ونتيجة تطبيق سياسة الرعاية التمريضية للعناية بالوصلة الشريانية الوريدية في المجموعتين الضابطة والتجريبية وذلك بعد 40 يوم من المتابعة باستخدام أداتين مطورتين هما استمارة البيانات الديموغرافية الحيوية واستمارة تقييم الوصلة الشريانية الوريدية. النتائج: أوضحت النتائج فعالية تطبيق سياسة العناية بالوصلة الشريانية الوريدية بعد العمل الجراحي. إذ انخفضت نسبة حدوث المضاعفات في المجموعة التجريبية بشكل ملحوظ إضافة إلى حدوث نضوج سريع للوصلة الشريانية الوريدية كان معظمها في اليوم العشرين من الدراسة بينما كانت هناك نسبة حدوث مضاعفات أعلى وتأخر في نضوج الوصلة الشريانية الوريدية إلى اليوم الأربعين من الدراسة وما بعد في المجموعة الضابطة التي تركت لروتين المستشفى. الاستنتاجات: تقترح معلومات الدراسة أن تطبيق سياسة الرعاية التمريضية بالوصلة الشريانية الوريدية بعد العمل الجراحي يساهم في خفض معدل حدوث المضاعفات ويسرع من نضوج الوصلة الشريانية الوريدية لدى مرضى الداء الكلوي النهائي. Although complications of arteriovenous fistula infrequent, but they occur, the most important and common complications are: thrombosis, infection, stenosis vascular, bleeding, aneurysm, ischemia. It was observed that preparation and good care of AVF have an important role in reducing complications in addition to accelerate the maturation of arteriovenous fistula. Implementing A protocol of Postoperative Arteriovenous Fistula Care Contributes in preventing complications and improve the maturation of arterial venous connection. Objective: This study was conducted to determine the effect of the application of the policy of nursing care on the clinical outcomes of the arterial venous connection postoperatively in patients with end stage renal disease. Goal: the aim of the present study was to determine the effect of Implementing A Protocol Of Postoperative Arteriovenous Fistula Careon clinical outcomes in patients with end stage renal disease. Materials and Methods: the study was conducted at AL-Assad University Hospital (Lattakia), a convent sample of 20 patientsin the renal dialysis department and the Department of Surgery. Clinical results for AVF were evaluated and the results of application policy of nursing care to of AVF in the control and experimental groups after 40 days of follow-up by using tow development tools: Sociodemographic Data and Arteriovenous Fistula Assessment Sheet. Results: our results demonstrated important of application of A Protocol Of Postoperative Arteriovenous Fistula Care. It decreased the complications in the experimental group and improve maturation of AVF mostly in the twentieth day of the study, while there was complications higher and delay in the maturation of AVF to the fortieth day of the study and after in the control group, which left for routine hospital. Conclusions and recommendations: our present study results advice to apply a protocol of Postoperative Arteriovenous Fistula Care because its affect in decrease and preventing complication in addition to improve maturation of AVF on ESRD patients.